Analisis Penurunan Tingkat Kecacatan untuk Produk Paper Core di PT. X - Abner Dikman Pinasthika; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2023)
PT. X is a company engaged in packaging production, specifically paper core, which was established in 2001. The production system of PT. X operates on a made-to-order principle, manufacturing products according to customer orders and specifications. The success of meeting customer needs is crucial for business progress and sustainability, making quality management increasingly important in business competition. It can enhance customer satisfaction, maintain company reputation, reduce production costs, and improve profitability. Production data from March to April 2023 revealed a 20% defect rate in the grinding, coating, and polishing processes for paper core production, with "unstuck" being the most common defect type. The DMAIC methodology is employed to address and provide solutions to reduce this defect percentage. Quality control processes at PT. X need to be enhanced to achieve higher efficiency and customer satisfaction. Factors contributing to the "unstuck" defect include machine calibration errors, paper breakage, raw material inspection processes, and raw material quality. Recommended solutions include objective recording of paper cutting precision, MTBF analysis to anticipate machine breakdowns, SOP creation for raw material inspection, procurement of equipment for viscosity testing of adhesives and paper moisture, vendor agreements on quality, and improved production planning with humidity control in storage warehouses. Implementation of these solutions is expected to reduce the production defect rate and enhance quality of paper core products at PT. X.